Cisplatin DNA damage and repair maps of the human genome at single-nucleotide resolution - Hu, Jinchuan (Proc Natl Acad Sci U S A, 2016)
Cisplatin is a major anticancer drug that kills cancer cells by damaging their DNA. Cancer cells cope with the drug by removal of the damages with nucleotide excision repair. We have developed methods to measure cisplatin adduct formation and its repair at single-nucleotide resolution. “Damage-seq” relies on the replication-blocking properties of the bulky base lesions to precisely map their location. “XR-seq” independently maps the removal of these damages by capturing and sequencing the excised oligomer released during repair. The damage and repair maps we generated reveal that damage distribution is essentially uniform and is dictated mostly by the underlying sequence. In contrast, cisplatin repair is heterogeneous in the genome and is affected by multiple factors including transcription and chromatin states. Thus, the overall effect of damages in the genome is primarily driven not by damage formation but by the repair efficiency. The combination of the Damage-seq and XR-seq methods has the potential for developing novel cancer therapeutic strategies.